Comparing changes in gene expression across three myeloid cell lines during monocyte-to-macrophage differentiation - Cosser, Duncan Alexander (My University, 2022)
Monocytes and macrophages exhibit wide heterogeneity in phenotype and function. Despite this variety, cells from model cell lines are often used in experiments without accounting for these differences. We therefore sought to characterize the gene expression profiles of three model myeloid cell lines as they differentiate from a monocyte-like state to a macrophage-like state in order to identify core pathways across cell lines central to the differentiation process, as well as pathways uniquely involved in differentiation in specific cell lines. Using an RNA-seq analysis pipeline we developed, we examined gene expression in three myeloid cell lines – HL60, U937, and THP-1 – during phorbol 12-myristate 13-acetate (PMA)-induced macrophage differentiation. Using gene expression data from three experiments which induced macrophage differentiation in cells from these cell lines using PMA, we constructed gene expression profiles for the cells before and after PMA treatment. We performed differential gene expression analysis to find the genes that are differentially expressed in differentiation, followed by pathway overrepresentation analysis to identify key pathways involved in this process. We identified 1789 genes which were differentially expressed in all cell lines, as well as 2131 genes marked as differentially expressed only in HL60 cells, 1711 in U937 cells, and 2159 genes uniquely differentially expressed in THP-1 cells. Through subsequent investigation of specific gene clusters, we found that there were conserved pathways involved in the monocyte-to-macrophage transition in all cell lines, particularly those involved in phagocytosis and adherence. All cell lines also downregulated maintenance pathways involved in DNA replication and cell cycle control, a behaviour associated with differentiation. Additionally, we found that there were differences in differentiation between the cell lines: the ribosome and oxidative phosphorylation pathways were strongly down-regulated during the transition in HL60 cells, and multiple different components in the cytokine-cytokine receptor interaction pathway were up- and down-regulated in THP-1 cells. A core gene expression profile is associated with PMA-induced differentiation of myeloid cell lines to a macrophage state. However, differentiation of HL60 and THP-1 cells also induces distinct changes in metabolism and cellular signalling. Our research recommends discretion in cross-comparison between experimental results incorporating gene expression studies of these myeloid cells.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Gene expression; Monocyte; Macrophages